Diseño de un sistema de control interno para el mejoramiento del área financiero-contable de la empresa Gráficas Vásquez Cía. Ltda - Soria Arteaga, Andrea Cristina (2013)
An effective tool that helps to improve the management of a company, is the financial internal control, the same should be timely, clear, simple, flexible and contribute to the achievement of entity objectives. Discussing the topic DESIGN OF INTERNAL CONTROL SYSTEM FOR IMPROVING FINANCIAL-ACCOUNTING AREA OF GRÁFICAS VÁSQUEZ. LTDA. it was based on COSO system, because it´s a forms new vision of general internal control and more specifically, in regard to accounting. Theoretical framework is developed, where we find the concepts taken from books, to design according to specific rules, the control system. Implemented the share of the COSO internal control.